2016
DOI: 10.1002/jclp.22290
|View full text |Cite
|
Sign up to set email alerts
|

“The Worst Experience of My Life”: The Internship Crisis and Its Impact on Students

Abstract: The implications of these findings for supporting students, working to resolve the internship crisis, and adapting policy are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 35 publications
0
10
0
Order By: Relevance
“…The most recent (Hamp, Stamm, Lin, & Christindis, 2016) identified 53.4% of participants as having dependents and 77.4% reported they were married or partnered. In a study on psychology’s internship imbalance, Parent, Bradstreet, Wood, Ameen, and Callahan (2016) found that family factors were a prevalent concern and that not matching to internship was associated with negative impact on family support systems, inability to plan for a family’s future, the need to delay starting a family, and potential difficulty with fertility. Given that work-family interactions have a role in psychologists’ professional development, it is worthwhile to examine their consequences.…”
Section: Work-family Concerns In the Psychology Pipelinementioning
confidence: 99%
See 1 more Smart Citation
“…The most recent (Hamp, Stamm, Lin, & Christindis, 2016) identified 53.4% of participants as having dependents and 77.4% reported they were married or partnered. In a study on psychology’s internship imbalance, Parent, Bradstreet, Wood, Ameen, and Callahan (2016) found that family factors were a prevalent concern and that not matching to internship was associated with negative impact on family support systems, inability to plan for a family’s future, the need to delay starting a family, and potential difficulty with fertility. Given that work-family interactions have a role in psychologists’ professional development, it is worthwhile to examine their consequences.…”
Section: Work-family Concerns In the Psychology Pipelinementioning
confidence: 99%
“…These concerns are particularly evident in the beginning of psychologists’ careers as they work to establish themselves in the profession. In addition to these factors those with families often experience stigma and discrimination due to their caregiver status (Jones, 2017; Parent et al, 2016). The bias is often covert and reflects a fear that the family role will threaten professional achievement (Parent, Weiser, & McCourt, 2015).…”
Section: Work-family Concerns In the Psychology Pipelinementioning
confidence: 99%
“…Much of the existing research on psychology trainees relies on data from large archival data sets collected by regulatory and professional organizations. Examples of archival data sets used in frequently published research on psychology trainees include Association of Psychology Post-doctoral and Internship Centers (APPIC) match data (Parent & Williamson, 2010), APPIC internship applicant survey data (Lund, 2021(Lund, , 2022bLund, Bouchard, & Thomas, 2016;Parent et al, 2016), and data from the APA Commission on Accreditation (APA, CoA; Andrews & Lund, 2015;Callahan et al, 2018; see also American Psychological Association Commission on Accreditation, n.d.). These data sets may either be publicly available or obtained through special request to the organization that collects the data (Andrews & Lund, 2015).…”
Section: Analysis Of Archival Datamentioning
confidence: 99%
“…There is a need for empirical research about professional psychology trainees and their experiences throughout the training process (Callahan & Watkins, 2018a, 2018b, 2018c. The data obtained in such studies can help answer questions about important topics such as admission and attrition patterns (Callahan et al, 2018), differential internship match rates (Callahan et al, 2010(Callahan et al, , 2014Dimmick & Callahan, 2022;Lund, 2021;Parent & Williamson, 2010), representation of different marginalized groups in psychology training (Andrews & Lund, 2015;Callahan et al, 2018), experiences of students participating in the predoctoral internship match (Lund, 2021;Parent et al, 2016), and student publication productivity (Lund, Bouchard, & Thomas, 2016). This research is especially critical for addressing issues related to diversity, equity, and inclusion (DEI) in professional psychology education and training (Callahan et al, 2018), including as it relates to disability and its intersection with other marginalized identities (Lund et al, 2023).…”
mentioning
confidence: 99%
“…Not matching to an internship the first year one applies creates a barrier to individuals seeking to not only finish their training but also to complete their training in their desired geographic location or training setting (Parent, Bradstreet, Wood, Ameen, & Callahan, 2016; Wells et al, 2014). Because internship spots were increasingly competitive in applicants’ desired area of focus and geographic locales during the crisis, individuals would often apply to and rank whatever internship was available to them to avoid the risk of not matching at all.…”
mentioning
confidence: 99%